THE EFFECT OF SERVICE QUALITY AND PROMOTION TOWARDS CUSTOMER DECISION - Pradaka, Izmi Fikadillah; Fachri, Helman (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the influence of service quality and promotion on consumer decision-making regarding the use of Lash by Vie services in Pontianak City. Using an associative research approach, the study gathered data from 100 female respondents who had previously utilized the salon's services. Multiple regression analysis was employed as the primary analytical method, using SPSS version 25. Validity and normality tests confirmed that all items were both reliable and normally distributed. The findings reveal that, individually (through T-tests), both service quality and promotion have a positive and significant impact on consumer decision-making. Furthermore, the F-test results demonstrate that, when considered together, service quality and promotion significantly and positively influence consumers' decisions. These results underscore the importance of both factors in shaping consumer choices regarding beauty services.